2016
DOI: 10.1111/jeb.12996
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific selection under environmental stress in seed beetles

Abstract: Sexual selection can increase rates of adaptation by imposing strong selection in males, thereby allowing efficient purging of the mutation load on population fitness at a low demographic cost. Indeed, sexual selection tends to be male-biased throughout the animal kingdom, but little empirical work has explored the ecological sensitivity of this sex difference. In this study, we generated theoretical predictions of sex-specific strengths of selection, environmental sensitivities and genotype-by-environment int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 88 publications
2
58
2
Order By: Relevance
“…Our findings that several pre‐ and postcopulatory sexually selected traits exhibit marked reductions in mean trait expression following diet restriction accord with a number of previous studies on guppies (Devigili et al ; Gasparini et al ) and other species (David et al ; Cotton et al ; Fox et al ). Numerous studies have reported that individuals whose condition is experimentally manipulated exhibit reduced mean trait expression and reproductive success, leading to an overall increase in the opportunity for sexual selection (Zikovitz & Agrawal ; Martinossi‐Allibert et al ). However, when the whole population experiences a reduction in the resources available for reproduction, whether the opportunity for selection increases will largely depend on the effect of resources on the variance in the expression of sexually selected traits, rather than on their mean (Arbuthnott & Whitlock ; Fox et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings that several pre‐ and postcopulatory sexually selected traits exhibit marked reductions in mean trait expression following diet restriction accord with a number of previous studies on guppies (Devigili et al ; Gasparini et al ) and other species (David et al ; Cotton et al ; Fox et al ). Numerous studies have reported that individuals whose condition is experimentally manipulated exhibit reduced mean trait expression and reproductive success, leading to an overall increase in the opportunity for sexual selection (Zikovitz & Agrawal ; Martinossi‐Allibert et al ). However, when the whole population experiences a reduction in the resources available for reproduction, whether the opportunity for selection increases will largely depend on the effect of resources on the variance in the expression of sexually selected traits, rather than on their mean (Arbuthnott & Whitlock ; Fox et al ).…”
Section: Discussionmentioning
confidence: 99%
“…; Martinossi‐Allibert et al. ). Sterilized females are able to compete with the focal females over egg laying substrate (i.e., seeds) and potential mating opportunities (personal observations).…”
Section: Methodsmentioning
confidence: 98%
“…Sexual conflict unfolds via two fundamentally distinct processes: intra‐locus sexual conflict (IASC), when the trait/s under sexually antagonistic selection share the same underlying loci (e.g., different optima for the same trait in males and females), or inter‐locus sexual conflict (IRSC), when sexually antagonistic selection targets different loci in both sexes (e.g., male adaptations involving one trait and female counter‐adaptations involving a different trait). Recent work has emphasized that both IASC and IRSC must be understood in its ecological setting (Gomez‐Llano, Bensch, & Svensson, ; De Lisle, Goedert, Reedy, & Svensson, ; Martinossi‐Allibert, Arnqvist, & Berger, ; Perry, Garroway, & Rowe, ; Perry & Rowe, ). On the one hand, several studies over the last few years have shown that IASC can be strongly modulated by the environment so that inter‐sexual correlations in fitness can change significantly across environments (Berger et al, ; Long, Agrawal, & Rowe, ; Punzalan, Delcourt, & Rundle, , but see Delcourt, Blows, & Rundle, ; Martinossi‐Allibert, Savkovic et al, ; Punzalan et al, ).…”
Section: Introductionmentioning
confidence: 99%